IMPACT OF QUR’AN RECITATION THERAPY ON PHYSIOLOGIC RESPONSES IN NEONATES ADMITTED IN NICU: A SYSTEMATIC REVIEW - Devi, Desriati; Rustina, Yeni (Journal of Islamic Nursing, 2019)
Abstract  Neonates who are admitted in NICU are exposed to tumultuous care environment originating from medical devices and procedures which may affect their physiological responses.This study aimed to identify the impact of Quran recitation therapy on physiological responses in neonates who were admitted in NICU. A systematic review was conducted by searching literatures of three databases including Science Direct, Scopus (2010-2018), and Google Scholar (2015-2018). The key words included “infants”, “holy Qur’an recitation”, and “Qur’an recitation” with inclusion criteria of literatures published in English language, Quasi-experimental study design, randomized controlled trials, neonates admitted in NICU as study sample, and impact of Quran recitation on physiological responses (oxygen saturation, respiratory rate, and pulse). The searching process resulted in 5 articles which met the inclusion criteria. The intervention of Quran recitation in those studies was performed once per day with duration of 10-25 minutes. The recited chapters included Al-Isra, Yusuf, Ar-Rahman, and Yasin. The intervention was provided through headphone with sound volume ranging from 45 to 65 dB. Four out of five studies reported significant difference. Qur’an recitation therapy had a significant effect on physiological responses in neonates admitted in NICU, including lower pulse and respiratory rate as well as higher oxygen saturation. The therapy may be provided as complementary and supportive intervention in order to improve stability of physiological responses in neonates admitted in NICU. Key words: Qur’an therapy; Physiological Responses; Neonates; NICU